The Analysis of Parking Facility Characteristic Areas for Academic Activity at Universitas Internasional Batam - Azzhara Amanda; Andri Irfan Rifai; Amanatullah Savitri (LPPM of NAROTAMA UNIVERSITY, 2023)
Purpose: Parking is an essential need that the community has for a motorist. The density of parking lots is often a problem with parking needs in a place. Universitas Internasional Batam, one of the campuses in Batam City, has a relatively small parking area. Thus, this study aims to analyze the need for parking lots in the Universitas Internasional Batam environment. Design/methodology/approach: The research method used is systematic observation guided by the Parking Space Unit (SRP) 1996. This research was carried out at night during the effective day of academic activity at Universitas Internasional Batam. Findings: Based on the results of studies that have been carried out, it is concluded that the area of land to be carried out for car parking planning at Universitas Internasional Batam covers an area of 8,169.45 m2 and has met the needs. In addition, the land to be planned for motorcycles parking covering an area of 1,574.69 m2 has also met the needs. Research limitations/implications: The planning and parking area at Universitas Internasional Batam have met vehicle parking needs. Practical implications: Factors due to the density of parking lots at Universitas Internasional Batam cause many vehicles to park on the shoulder of the road (on-street). Originality/value: This paper is an original work. Paper type: Research papers.